Impact of Agroforestry on the Natural Chemical Fertility of Cocoa Plantation Soils in Toumodi, Côte d’Ivoire - N’ganzoua Kouame Rene; Kouame Amany Guillaume; Voui Bi Bianuvrin Noel Boue; Bakayoko Sidiky (Research Advances and Challenges in Agricultural Sciences Vol. 8, 2024)
The aim of the study was to assess the impact of cocoa-based agroforestry systems on natural soil fertility. The experiment was carried out in the field from June to August 2020 in three types of cocoa-based agroforestry systems over 35 years old identified in Toumodi (Côte d’Ivoire) between latitudes North 6°19’37 and 6°34’51 and longitudes West 5°19’58 and 5°20’02 in the forest-savanna transition zone. The methodology consisted of identifying three cocoa-based agroforestry systems (simple, mixed or complex) guided by the opening of the canopy of the various floristic species associated with cocoa trees, in which three 100 m2 plots were randomly laid out to inventory the arboricultural species encountered, and in each case auger soil samples were taken from the 0-20 cm and 20-40 cm horizons for laboratory analysis. The results identified 17 arboricultural families (Anacardiaceae, Apocynaceae, Arecaceae, Bombacaceae, Caricaceae, Combretaceae, Euphorbiaceae, Invingiaceae, Lauraceae, Meliaceae, Mimosaceae, Moraceae, Musaceae, Myristicaceae, Rutaceae, Sterculiaceae, Verbenaceae) divided into 27 plant species, 55.55% of which are planted in simple agroforestry systems (SAGS) with a density of 55 trees/hectare, 70.37% in mixed agroforestry systems (MAGS) with a density of 155.33 trees/hectare and 81.40% in complex agroforestry systems (CAGS) with a density of 224.33 trees/hectare. The arboricultural species introduced or maintained in the plantations are generally species with shade, food, economic or medicinal interests. Chemically, the levels of major elements, trace elements and clay-humus complex generated in the soil were satisfactory at depths of 0-20 cm and 20-40 cm, whatever the agroforestry system, but in decreasing order in MAGS, CAGS and SAGS. The various positive (R=0.80) or negative (R=-0.80) correlations established between the mineral elements in the superficial horizons contribute to soil enrichment through synergistic or antagonistic effects in the agroforestry systems of Toumodi, Côte d’Ivoire. The study shows that each forest agroforestry system has its own distinct characteristics, which can be summed up mainly in its floristic diversity and density of associated trees, and are as follows The study shows that each forest agroforestry system has its own distinct characteristics, mainly in terms of floristic diversity and density of associated trees, and that they all not only preserve a certain level of biodiversity and chemical fertility of the soil but much more so at 0-20 cm than at 20-40 cm. Moreover, MAGS is the best agroforestry system that can be recommended during the establishment of cocoa plantations in Côte d’Ivoire.